Development of Bi-hexagonal hybrid crash box subjected to axial loading for enhancement of crashworthiness - Choiron, Moch Agus; Wakhidah, Delia Hani; Nurchajat (Eastern-European Journal of Enterprise Technologies, 2023)
Crash box design had been developed to increase crashwortiness performance. The crash box cross section is one important parameter to increase the energy absorption as crashwortiness performance. In the previous study, hexagonal cross section provide the higher energy absorption than other cross section. One of strategy to increase cross section is using two cross section put together in one component of crash box design. Bi-tubular crash box shows higher energy absorption with easy manufacture opportunity. In other study, hybrid crash box is investigated to reduce crash box mass. In this study, development of bi-hexagonal hybrid crash box subjected to axial loading to enhance crashworthiness were investigated. Analysis of crash box design is developed by using computer simulation with ANSYS Workbench 19.2. The crash box materials used are Aluminum Alloy and carbon-epoxy woven. The material modeling in the crash box is assumed as deformable body while the impactor is a rigid body. The axial loading is modelled by setting impactor impact the crash box with a speed of 7.67 m/s. Fixed support is set on the bottom of crash box. Nine of frontal test models were simulated for the bi-hexagonal hybrid crash box with different layups orientation angle and composite hexagonal tube diameter. Energy absorption and deformation patterns were observed. The results indicated that the highest energy absorption and specific energy absorption is occured on the A60 model with layups orientation angle of [0/60/0/60] and composite hexagonal tube diameter of 41 mm are 3693.8 J and 19.121 kJ/kg. The deformation pattern in the aluminum part is diamond mode, while in the composite part, the deformation pattern produce transverse shearing, lamina bending, brittle fracturing and local buckling mode